2022
DOI: 10.1186/s13690-022-00804-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of surge adaptations on hospitalist care teams during the COVID-19 pandemic utilizing a rapid qualitative analysis approach

Abstract: Background Hospital systems have rapidly adapted to manage the influx of patients with COVID-19 and hospitalists, specialists in inpatient care, have been at the forefront of this response, rapidly adapting to serve the ever-changing needs of the community and hospital system. Institutional leaders, including clinical care team members and administrators, deployed many different strategies (i.e. adaptations) to manage the influx of patients. While many different strategies were utilized in hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…The focus of conversations in all three categories is on prescribing and evaluating the results of various tests. Regression analysis showed that the outpatient consultation time of cancer patients who only came for admission procedures was shorter, because the admission process was simpler, and doctors may also prefer simplified communication strategies in the outpatient environment compared with the doctor-patient interaction after the patient was hospitalized [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The focus of conversations in all three categories is on prescribing and evaluating the results of various tests. Regression analysis showed that the outpatient consultation time of cancer patients who only came for admission procedures was shorter, because the admission process was simpler, and doctors may also prefer simplified communication strategies in the outpatient environment compared with the doctor-patient interaction after the patient was hospitalized [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used rapid qualitative methods, which have been reported by others and used by our group. [15][16][17][18][19] These methods have been shown to be useful in dynamic, rapidly changing situations. 15,18,19 This design allowed us to assess focus group participants' experiences on APP utilization and how billing reforms had directly impacted participants.…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17][18][19] These methods have been shown to be useful in dynamic, rapidly changing situations. 15,18,19 This design allowed us to assess focus group participants' experiences on APP utilization and how billing reforms had directly impacted participants. Our study was designed to deliver focused and actionable findings from the focus groups.…”
Section: Methodsmentioning
confidence: 99%
“…Following the focus groups, we utilized a rapid qualitative analysis process to analyze the content of the focus groups, applying methods similar to prior work. [17][18][19][20] Rapid qualitative methods have been previously described, consisting of a structured analysis that can be useful in situations of dynamic, rapidly changing real-world situations (such as a pandemic). 18,21 Templated summaries were created for each of the interviews and focus groups.…”
Section: Ranking and Analysismentioning
confidence: 99%